(untitled) (Medico Legal Update, 2019)
Introduction: Aggression is a professional hazard for those who are employed in the psychiatric setting. There is evidence that 52% of the nurses working in the emergency department experience physical or other violence from clients. There are not many studies conducted in India regarding the application of aggression management training in a psychiatric setting. Material and Method: A quantitative method was used for implementing a participatory training programme. There were 44 trainer group nurses and 138 trainee group nurses from psychiatric, emergency and intensive care settings. The trainer group nurses were trained by the investigator and the trainee group nurses were trained by the trainer group nurses. An interpretive exercise was developed and validated to assess the competency of the nurses on aggression management and violence prevention. There were two posttests for the trainer group nurses and there was one posttest for the trainee group nurses. Results: Among the trainer group nurses, majority (93.2%) of the nurses were non-competent during the pre-test. But all the nurses (100%) were competent during the post-test one and the post-test two. Among the trainee group nurses, majority (97.1%) of the nurses were non-competent during the pre-test and all the nurses (100%) were competent during the post-test. Majority of the key personnel (82%) opined that, their staff perform better aggression management practices after the training programme. Conclusion: An aggression management and violence prevention (AMVP) training programme based on participatory approach was found to be more effective to empower the nurses to work in psychiatric and emergency settings.